2020
DOI: 10.1002/pbc.28329
|View full text |Cite
|
Sign up to set email alerts
|

Trends in conditional survival and predictors of late death in neuroblastoma

Abstract: Purpose Significant advances in the treatment of neuroblastoma have been made in the past several decades. There are scant data examining how these improvements have changed over time and differentially affected conditional survival among high‐risk and non‐high‐risk patient groups. Methods We conducted a retrospective cohort study using the Surveillance, Epidemiology, and End Results database. We analyzed clinical characteristics and survival outcomes for 4717 neuroblastoma patients. Kaplan‐Meier methods were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…17 less than 10% for relapsed populations, expeditious and efficient trials are of the utmost importance. 18,19 We observed that only GD2 antibodies, B7-H3-targeted radiopharmaceutical, MIBG, isotretinoin and ALK inhibitors were advanced to evaluation in the phase 3 setting, and only GD2 antibodies and isotretinoin have thus far become front-line standard of care. Over our study period, only five phase 3 trials were identified, reflecting both the rarity of this disease and the complexities of initiating these trials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17 less than 10% for relapsed populations, expeditious and efficient trials are of the utmost importance. 18,19 We observed that only GD2 antibodies, B7-H3-targeted radiopharmaceutical, MIBG, isotretinoin and ALK inhibitors were advanced to evaluation in the phase 3 setting, and only GD2 antibodies and isotretinoin have thus far become front-line standard of care. Over our study period, only five phase 3 trials were identified, reflecting both the rarity of this disease and the complexities of initiating these trials.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these trials were academically sponsored and were not trans-Atlantic, reflecting the general picture in pediatric oncology of a lack of academically sponsored trans-Atlantic trials. 18,20 Efforts to facilitate trans-Atlantic trials are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Improving survival over time as demonstrated by epidemiological and other studies can also be partly attributed to major changes in standard of care-including transplant. [23][24][25][26]…”
Section: Analyzing the Evidencementioning
confidence: 99%